Liquidity regulation and banks: Theory and evidence - Sundaresan, Suresh; Xiao, Kairong (Journal of financial economics, 2024)
This paper theoretically and empirically investigates the effects of liquidity regulation on the banking system. We document that the current quantity-based liquidity rule has reduced banks' liquidity risks. However, the mandated liquidity buffer appears to crowd out bank lending and lead to a migration of liquidity risks to banks that are not subject to liquidity regulation. These findings motivate a model of liquidity regulation with endogenous liquidity premiums and heterogeneous banks. The model shows that the current liquidity rule can improve upon the unregulated equilibrium but can also have distortionary effects because of the dual role of the liquidity buffer as an implicit tax and a costly mitigator of liquidity risks. The fixed quantity mandate can interact with the uncertain liquidity demand, amplifying the volatility in the liquidity premium. A central bank committed liquidity facility could improve the current quantity-based regulation by introducing a price-based mechanism.